Estudo de propriedades críticas para modelos de rede com estados absorventes - Dantas, Wellington Gomes (2006)
In this work we study the phase transitions between an absorbing and an active state in markovian lattice models. We investigate two different categories of these models: with conserved number of particles and with fluctuating number of particles. In particular, we study variations of the contact process and the Manna sandpile, two icons of the systems that undergo phase transitions in nonequilibrium regime. Using techniques such as mean-field approximations, numerical simulations, exact diagonalization and series expansions we access the universality classes for these cases.